DETERMINANTS OF SUPPLY AND DEMAND AND PRICES FOR SOME MAJOR CROPS IN GLOBAL MARKETS FOR THE PERIOD (1990-2010) - Lora AI-Saor; Salim Y. Sultain AI-Niaamy (Mesopotamia Journal of Agriculture)
Supply and demand analysis is of a great importance in economic studies, especially the supply and demand of grain crops strategy in the global market because of its close link themes of food security and strategic stocks, and prices play an important role in influencing the volume of production, consumption and distribution in the structure of economic communities. This research adopted on analysis quantitative and economic method to achieve the objectives. The analysis has found that the trend overall time for each of the rate of growth of production and consumption has taken a growing trend rate (35.8) and (29.2) million tons, respectively. The results showed significant variables acreage and technological development in the influence function display World cereal and by (86.3%) of the total changes, as shown by significant variable size of the population only in function of global demand and by (89.6%) of the total changes, either for variables of global supply and global demand for grain only noon legal entities in their impact on the function world prices. The study  reached at a set of findings and recommendations.